2018
DOI: 10.1007/s10554-018-1379-0
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular function and mechanics in chemotherapy- and radiotherapy-naïve cancer patients

Abstract: The present research evaluated right ventricular (RV) structure, function and mechanics in the cancer patients before initiation of chemo- or radiotherapy, and the association between cancer and decreased RV longitudinal strain. This retrospective investigation included 101 chemo- and radiotherapy-naïve patients with solid cancer and 38 age- and gender-matched controls with similar cardiovascular risk profile. Echocardiographic examination and strain evaluation was performed in all participants. RV structure a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 29 publications
0
23
0
3
Order By: Relevance
“…Left ventricular (LV) remodeling in the treated cancer patients has been confirmed in the large number of studies [1,2,3], and particularly important is the incremental predictive value of LV changes in the cancer patients [3]. Our study group recently showed that left and right ventricular functional impairment, particularly in strain, was present in the cancer patients before anti-cancer therapy [4,5]. However, LA remodeling in these patients is still a matter of debate [2,6].…”
Section: Introductionmentioning
confidence: 87%
“…Left ventricular (LV) remodeling in the treated cancer patients has been confirmed in the large number of studies [1,2,3], and particularly important is the incremental predictive value of LV changes in the cancer patients [3]. Our study group recently showed that left and right ventricular functional impairment, particularly in strain, was present in the cancer patients before anti-cancer therapy [4,5]. However, LA remodeling in these patients is still a matter of debate [2,6].…”
Section: Introductionmentioning
confidence: 87%
“…However, few studies regarding three‐layer RV‐GLS have been reported thus far. Guerra et al found that the impairment of three‐layer GLS in patients with systemic sclerosis was homogeneous in the RV and heterogeneous in the LV (GLS‐epi most impaired), while Tadic et al demonstrated that a significant deterioration of RV‐GLS occurred in the endocardium and mid‐myocardium in chemo‐ and radio‐therapy‐naive patients with solid cancer. A reasonable explanation of these conflicting data, on one hand, could be the differences in cardiovascular risk factors and demographics of the study patients.…”
Section: Discussionmentioning
confidence: 99%
“…LV circumferential and radial strains were not assessed in this study. 4,5 The difference existed not only in the global values of LV and RV strains, but also in layer-specific strain, which further implies transmural myocardial and not endocardial impairment, as it was usually presumed. Mavinkurve-Groothuis et al reported a significant reduction in LV longitudinal, circumferential, and radial strains in the children with acute lymphoblastic leukemia after anthracycline therapy than before treatment.…”
Section: Left Ventricular Dysfunction Before Chemotherapy: Did We Mismentioning
confidence: 96%
“…3 Our research group recently published studies in which it was shown not only that LV multidirectional strain (longitudinal, circumferential, and radial) was significantly decreased in chemotherapy-and radiotherapy-naïve patients with solid cancer, but also that right ventricular (RV) longitudinal strain was significantly reduced in the cancer patients in comparison with controls. 4,5 The difference existed not only in the global values of LV and RV strains, but also in layer-specific strain, which further implies transmural myocardial and not endocardial impairment, as it was usually presumed.…”
mentioning
confidence: 96%